Ex situ liver resection and partial liver autotransplantation for advanced cholangiocarcinoma - Mustafa Ozsoy (Nigerian Journal of Surgery, 2019)
Surgery is the only known curative treatment option for cholangiocarcinoma. Ex situ liver surgery and autotransplantation are promising approaches in cases that cannot be treated by conventional methods and particularly in the presence of centrally localized liver tumors as well as tumors that invade the main vascular structures. A 53-year-old female patient presented with abdominal pain and nausea. Abdominal tomography showed a tumoral mass lesion that filled the left lobe of the liver and invaded the left hepatic vein and the inferior vena cava. Cholangiocarcinoma diagnosis was reached based on biopsy findings, and the patient was scheduled for surgery as positron emission tomography did not indicate any other disease focus. The patient underwent ex situ liver resection and autotransplantation. She was discharged on the 7th postoperative day. A 68-year-old male presented with abdominal pain, weakness, and weight loss. Laboratory analysis indicated elevated carbohydrate antigen 19-9: 400 U/ml and alpha-fetoprotein (AFP): 2000 U/ml, and there was no other pathology. Abdominal tomography showed a mass that filled the center of the liver and invaded the left hepatic vein and the inferior vena cava. Pathological findings of the biopsy sample were reported as combined hepatocellular-cholangiocellular carcinoma. The patient's AFP levels continued to increase despite transcatheter arterial chemoembolization and radiofrequency ablation therapy. Surgery was decided as indocyanine green clearance test, and the result was 8.5%. He underwent ex situ liver resection and autotransplantation. Unfortunately, he died on the 4th postoperative day due to respiratory failure. Ex vivo liver resection and partial liver autotransplantation should be considered for the surgical treatment of locally advanced cholangiocarcinomas that invaded the main vascular structures.